2018
DOI: 10.1007/s00300-018-2287-4
|View full text |Cite
|
Sign up to set email alerts
|

Insight into heavy metal resistome of soil psychrotolerant bacteria originating from King George Island (Antarctica)

Abstract: The presence of heavy metals in Antarctica is an emerging issue, especially as (bio)weathering of metal-containing minerals occurs and human influence is more and more visible in this region. Chemical analysis of three soil samples collected from the remote regions of King George Island (Antarctica) revealed the presence of heavy metals (mainly copper, mercury, and zinc) at relatively high concentrations. Physiological characterization of over 200 heavy metal-resistant, psychrotolerant bacterial strains isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 70 publications
2
46
1
Order By: Relevance
“…This suggests that plasmid transfer involving bacteria of the Comamonadaceae family in polar regions may be limited by narrow host range of their replicons. Interestingly, the majority of plasmids of Arctic and Antarctic bacteria examined in our previous studies also had a narrow host range ( Dziewit et al, 2013a , b ; Ciok et al, 2016 ; Romaniuk et al, 2018 ), which may suggest that this phenomenon is more common.…”
Section: Discussionmentioning
confidence: 81%
“…This suggests that plasmid transfer involving bacteria of the Comamonadaceae family in polar regions may be limited by narrow host range of their replicons. Interestingly, the majority of plasmids of Arctic and Antarctic bacteria examined in our previous studies also had a narrow host range ( Dziewit et al, 2013a , b ; Ciok et al, 2016 ; Romaniuk et al, 2018 ), which may suggest that this phenomenon is more common.…”
Section: Discussionmentioning
confidence: 81%
“…Essential heavy metals such as zinc, copper, iron, and chromium are important to life. They play an integral role in metabolic processes and are essential micronutrients and cofactors of several enzymes, required in redox processes and stabilization of molecules through electrostatic interactions and regulation of osmotic pressure (Bruins et al 2000;Romaniuk et al 2018). However, heavy metals with no known biological function such as mercury are very toxic to the cell.…”
Section: Introductionmentioning
confidence: 99%
“…ANT_H30 and Rhodococcus sp. ANT_H53B, originated from a collection of bacterial cultures that were previously isolated from soil samples taken in 2012 from King George Island (Antarctica, GPS coordinates: 62°09.601′ S, 58°28.464′ W) [ 21 ]. The strains are orange pigmented ( Figure 1 ), which suggested that they are carotenoid producers.…”
Section: Resultsmentioning
confidence: 99%